Beyond Information Warfare: Exploring Fact-Checking Research About the Russia–Ukraine War - Ricardo Morais; Valeriano Piñeiro-Naval; David Blanco-Herrero (Journalism and Media)
The Russian invasion of Ukraine has also ignited a battleground in the domain of information. The conflict has been accompanied by a relentless disinformation offensive designed to manipulate public opinion and undermine democratic processes. This paper deals with the role of academia and scholars in focusing this information warfare. This study conducts a comprehensive analysis of scientific articles to examine how researchers and institutions have addressed fact-checking initiatives. To this end, performance analysis and literature review are combined to observe the state of academic investigations on fact-checking during the first thousand days of war in Ukraine (from 24 February 2022 to 19 November 2024). To do this, we identified 595 fact-checking articles in the Web of Science database within the “Social Sciences” category and narrowed the focus to 270 articles in the field of “Communication”. Finally, through an in-depth literature review of eight manuscripts, we seek to understand the specific strategies employed by academics to address the conflict between Russia and Ukraine through fact-checking. Our findings suggest that fact-checking research on the Russia–Ukraine war predominantly examines the impact of disinformation in conflict contexts, the role of media literacy in countering false narratives, and the contribution of citizen journalism to verification efforts. These conclusions can shed light on the crucial role of academia in safeguarding truth and fostering informed public debate in an era of information overload and manipulation.